A System to Support Policy Development for the Sustainable Production of Biofuels - Singh , MINERVA; BANARES -ALCANTARA, RENO; SKRZYPCZAK, SIMON; ALDEA, ARANTZA (Asian Journal of Chemistry, 2010)
The authors present a system that supports the development of policies, in particular those related to food security. It does so by facilitating the communication between policy makers through the explicit computer representation of policy intent, content and rationale. A prototype software system has been implemented as an extension of Compendium (http:// compendium.open.ac.uk) and its potential impact as a tool to be used during policy making is explained with the help of a case study on the sustainable production of biofuels in Zambia.